Research Ethics and Commercial Drug Development: When Integrity Threatens Profitability - Bélisle Pipon, Jean-Christophe (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
This case, based on personal experiences and on those found in the literature, highlights the delicate tension faced by drug development companies having to balance research integrity and their profitability.